Memorandum of understanding between Universiti Teknologi MARA and MyBamboo Sdn. Bhd. / Fakulti Kejuruteraan Awam - Universiti Teknologi MARA, Fakulti Kejuruteraan Awam (Universiti Teknologi MARA (UiTM), 2019)
The principal purpose of this MoU is to promote collaborative co-operation between UiTM and MyBamboo Sdn Bhd with the following objectives: 1. Create smart partnership 2. Promote industry-university knowledge sharing 3. Enhance cooperation and collaboration in research development and commercialization of research 4. Share respective resources and expertise